Implementasi Tata Tertib Sekolah dalam Membentuk Karakter Disiplin Siswa - Hidayah, Nur; Sukari, Sukari; Subando, Joko (TSAQOFAH, 2026)
School rules constitute a set of regulations designed to guide student behavior and create an orderly, safe, and conducive learning environment, thereby playing a strategic role in shaping students’ disciplinary character. This study aimed to describe the implementation of school rules and analyze their contribution to the formation of students’ disciplinary character at MTs Sholihiyyah Kalitengah Mranggen Demak. The study employed a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation, drawing on sources including the principal, teachers, students, and school records. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings show that the implementation of school rules is carried out through socialization, habituation, supervision, and the application of reward-and-sanction systems, all of which demonstrably contribute to the development of students’ disciplinary character. This contribution is evident in improved punctuality, compliance with dress codes, orderliness during learning activities, and respectful attitudes toward teachers. The main supporting factors include teachers’ role modeling, parental involvement, and a positive school environment, while inhibiting factors comprise low awareness among some students, inconsistencies in rule enforcement, and negative influences from outside the school environment. The study concludes that school rules implemented consistently and supported by exemplary conduct and school–parent collaboration play an important role in strengthening students’ disciplinary character at madrasah tsanawiyah and can serve as a basis for developing more systematic character education policies.